THE EFFECT OF WORK-LIFE BALANCE ON JOB SATISFACTION WITH BURNOUT AS AN INTERVENING VARIABLE - Frizi Arya Denandra; M. Sudirman; Rina Masruroh (Cirebon International Conference on Education and Economics Proceeding, 2024)
The problem in this research is that maximum job satisfaction has not been achieved by Bank Kuningan. This issue is affected by multiple factors, including the work-life balance and burnout. The objective is to determine the impact of work-life balance on job satisfaction via the mediating role of burnout as a third party. The methodology employed by scientists is the survey method. The population of this investigation was all of the 103 employees at Bank Kuningan, this technique was employed to collect a large number of participants. Data was gathered via a questionnaire that was considered valid and dependable. The method of data analysis employed is path analysis. The results of this study state that (1) Work-life balance positively and significantly affects job satisfaction; (2) work-life balance negatively and significantly affects burnout; (3) burnout negatively and significantly affects job satisfaction; and (4) burnout partially mediates the relationship between work-life balance and job satisfaction.